Association between chronic kidney disease and sarcopenia and emerging treatment strategies - Li, Shuxin; Cao, Hongliang; Gao, Zihan; Liang, Yuwei; Ma, Yutao; Liu, Shanyu; Wang, Liming; Wei, Wei (Frontiers in Nutrition, 2025)
Chronic kidney disease (CKD) is an irreversible and progressive kidney disease with a significant global health impact. Sarcopenia is an age-related syndrome characterized by the progressive loss of skeletal muscle mass and strength, and it exhibits a high prevalence, particularly among the elderly. There is a growing body of evidence indicating a strong bidirectional association between CKD and Sarcopenia. The prevalence of sarcopenia is significantly higher in CKD patients and increases as kidney function deteriorates. This review examines the potential relationship between CKD and sarcopenia, discusses their pathophysiological mechanisms, including chronic inflammation, oxidative stress, uremic toxin accumulation, metabolic acidosis, and hormonal disorders, and explores their clinical implications. Additionally, this review aims to elucidate potential pathogenic mechanisms and propose preventive and therapeutic strategies for CKD and sarcopenia, thereby guiding the optimization of clinical management and slowing disease progression.